Estimation of technical conditions of two-shaft by-pass turbojet engine according to the parameters which are registered on transition regime - Дмітрієв, С. О.; Моісєєв, Б. М.; Салім Ханна, Абу Хайдар; Шаабдієв, С. Ш. (Proceedings of National Aviation University (archive), 1998)
Proposed is the methodics of diagnosis of two-shaft engine as to the complex dynamic parameter. Shown are the results of instrumental research on АИ-25 engine by the worked out methodics of estimation.